Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.ijsu.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless thyroidectomy

Abstract: The ultrasonic scalpel and the Ligasure ares safe, effective, useful, and time-saving alternative to the traditional suture ligation technique for thyroid surgery. They simplified total thyroidectomy, eliminating the need for clamp-and-tie maneuvers while achieving efficient hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…In our study, we used two innovative devices, which led great results in terms of accuracy of hemostasis and reducing of operative time both in young and in elderly patients. We already proved this promising result, in younger patients [5]; in the present study we found that the use of hemostatic and dissecting devices such as Harmonic Focus or Ligasure Precise/Small Jaw in geriatric thyroidectomy is as safe as traditional surgery and faster than it, allowing a shorter anesthesia and a possibility to save time for other surgery in a single center. Regarding possible differences between the elderly and the younger groups, we found no statistically significant differences about rates of postoperative complications, such as hemorrhage, seroma, hematoma, wound infection, transient or definitive hypocalcaemia, transient or definitive recurrent nerve palsy.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In our study, we used two innovative devices, which led great results in terms of accuracy of hemostasis and reducing of operative time both in young and in elderly patients. We already proved this promising result, in younger patients [5]; in the present study we found that the use of hemostatic and dissecting devices such as Harmonic Focus or Ligasure Precise/Small Jaw in geriatric thyroidectomy is as safe as traditional surgery and faster than it, allowing a shorter anesthesia and a possibility to save time for other surgery in a single center. Regarding possible differences between the elderly and the younger groups, we found no statistically significant differences about rates of postoperative complications, such as hemorrhage, seroma, hematoma, wound infection, transient or definitive hypocalcaemia, transient or definitive recurrent nerve palsy.…”
Section: Discussionsupporting
confidence: 67%
“…Even though this increased risk appears to be related to the presence of comorbidities rather than to age alone [2], it should be preferred to reduce operative time and postoperative pain, guaranteeing at the same time the accuracy of hemostasis [4]. Besides the traditional surgical hemostatic techniques, different hemostatic approaches, which further minimize the risk of bleeding and complications during thyroidectomy, have become available [5]. These include the ultrasonic scalpel and the bipolar e radiofrequency sealing system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various EBDs, such as the harmonic scalpel or the electrothermal bipolar vessel sealing system, have been developed and shown to be superior to conventional suture ligation or electrocautery techniques in terms of decrease in operative time, hospital stay, blood loss, postoperative drainage, pain, and incidence of hypocalcemia. [24][25][26][27][28] However, EBDs now widely available in all operating rooms have the potential for visibly undetectable and heat-related collateral/proximity iatrogenic injury to adjacent structures. 13 In this study, we demonstrated that using the CIONM was useful in providing real-time EMG status correlates of heat thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…28,32 Extensive dissection in these patients will increase the risk of complications, for instance, accessory nerve injury, chyle leakage, skin numbness around the ear, neck and shoulder. [33][34][35][36] When performing lymph node dissection, it is necessary to make clear the scope of dissection, grasp the clear anatomical hierarchy, and protect the vascular branches and nerves. Therefore, in order to ensure the surgical benefit of patients, single regional or several sub-regional lymph node dissections is feasible for PTC patients with SLNM.…”
Section: Discussionmentioning
confidence: 99%